DAMPAK PERILAKU MENYIMPANG PADA PENDIDIKAN GENERASI MUDA DI DESA PUSUAGA DISTRIK KURIMA KABUPATEN YAHUKIMO - Haselo, Hermas (HOLISTIK, Journal Of Social and Culture, 2014)
To createinformed and the importance of education as the basis lives of the communityand young generations existing Desa Kurima Distrik Pusuaga Kabupaten Yahukimo,there are several factors that inhibits the impact of the entry of younggeneration is the negative influence from outside of them drinking alcoholicbeverages, night or discotheque hold the event, mini snub nose, inhaling glueaibon / castol, gambling play and promiscuity free, this means that manychildren who drop out of them from SD, SMP, SMA, even some also breaking up ofcollege.Social gap;a shift the value of the traditional society to modern cannot be separated fromthe influence of the influence of modernization and globalization, if there wassome individual who follows the influence will happen social gap .Social gap wouldcause the distance between the rich and the poor and it was damaged thediversity that is singular of the people of IndonesiaThegovernment and indigenous leaders have to do the act of the arrangement backthe life people in those on the lives of the younger generation with customaryimposed sanctions against the whole community who commits an offense of mannersof life that applies.Governmentsmust provide facilities of education, an adequate the teachers enough and goodthe provision of school near with residential areas and provide scholarships,educational assistance, give stimulation of the tourist visits regions forevery students achievement.Keywords:community, government, social gap